AB0262 Verification of Antibacterial Effect of Sulfasalazine in Rheumatoid Arthritis Patients. (15th July 2016) - Kitada, A.; Min, C.; Kataoka, Y.; Kaneshita, S.; Suda, M.; Takasugi, K.; Ohara, Y.; Rokutanda, R.; Shimizu, H.; Tsuda, T.; Kishimoto, M.; Yamaguchi, K.; et al.
Abstract : Background: Sulfasalazine (SSZ) might have antibacterial effect, because it contains sulfa residue. However, its clinical usefulness in patients of rheumatoid arthritis (RA) has been unclear. Objectives: Our aim was to evaluate whether SSZ could prevent bacterial infections especially in newly diagnosed RA patients. Methods: The adult patients who were newly diagnosed with RA at St. Luke's International Hospital, Tokyo, Japan from January 2006 to December 2013 were included in this retrospective open cohort study. The patients were divided into two groups, either SSZ group in which the treatment was started with SSZ or non-SSZ group in which the treatment was started with DMARDs except for SSZ. The diagnosis of infections was defined by the prescription of antibiotics. We investigated whether SSZ group showed lower incidence rate of infections compared to non-SSZ group by multivariate logistic regression analysis for well-known risk factors for infections, such as age and other immunosuppressive DMARDs use. Results: There were 179 eligible patients in SSZ group and 157 patients in non-SSZ group. Mean ages were 57.3±15.8 and 55.1±15.1 years old, and male percentages were 23.0 and 17.8% in SSZ group and non-SSZ group, respectively. Percentages who had received additional immunosuppressive agents including csDMARDs and bDMARDs were 68.2 and 86.0% for each groups. Incidence rate of bacterial infection was prone to be lower in SSZ group than in non-SSZ group in univariate analysis (17.7 per 100 person-years vs. 26.3 per 100 person-years, p=0.07). However, prevalence of infections in SSZ group did not differ from that of non-SSZ group both in univariate and multivariate analysis (0.30 vs. 0.30, p=0.49, 95% CI 0.51–1.37). Conclusions: SSZ did not prevent bacterial infections in newly diagnosed RA patients. Disclosure of Interest: A. Kitada Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, C. Min Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, Y. Kataoka Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, S. Kaneshita Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, M. Suda Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, K. Takasugi Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, Y. Ohara Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, R. Rokutanda Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, H. Shimizu Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, T. Tsuda Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, M. Kishimoto Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, K. Yamaguchi Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none, M. Okada Shareholder of: none, Grant/research support from: none, Consultant for: none, Employee of: none, Paid instructor for: none, Speakers bureau: none